2
$\begingroup$

I am a rookie so I hope you know the answer! Okay so from C. Möller and Landau & Lifshitz I have gathered that: $$ \gamma_{ij}=g_{ij}-\frac{g_{0i}g_{0j}}{g_{00}} \quad \gamma^{ij}\gamma_{jk}=\delta^i_k\quad \gamma^{ij}=g^{ij}\quad\gamma = \textbf{det}(\gamma_{ab}) = \frac{1}{\textbf{det}(\gamma^{ab})}\\ \epsilon_{ijk} = \epsilon^{ijk}=\left\{\begin{array}{ll} 1 & \text{if } (i,j,k) \text{ is an even permutation of } (1,2,3) \\ -1 &\text{if } (i,j,k) \text{ is an odd permutation of } (1,2,3) \\ 0 & \text{otherwise} \end{array}\right.\\ \varepsilon_{ijk}=\sqrt{\gamma}\epsilon_{ijk}\quad \varepsilon^{ijk}=\frac{1}{\sqrt{\gamma}}\epsilon^{ijk}\\ [\textbf{curl}(\textbf{v})]^{i}=\varepsilon^{ijk} v_{k,j}=\frac{1}{2}\varepsilon^{ijk}(v_{k,j}-v_{j,k})\quad\textbf{div}(\textbf{v})=\frac{1}{\sqrt{\gamma}}[\sqrt{\gamma} v^i]_{,i} $$

Can you similarly define $$ [\mathbf{curl}(\mathbf{\tilde{v}})]_i =\varepsilon_{ijk}v^{k,j} $$ And thereafter $$ [\mathbf{curl}\circ\mathbf{curl}(\mathbf{\tilde{v}})]^a=\varepsilon^{abc} [\varepsilon_{cde}v^{e,d}]_{,b}\\ [\mathbf{curl}\circ\mathbf{curl}(\mathbf{v})]_a=\varepsilon_{abc} [\varepsilon^{cde}v_{e,d}]^{,b} $$ And if so, what is the partial derivative of $\sqrt{\gamma}$ and $\frac{1}{\sqrt{\gamma}}$? Is it valid to reexpress the equations above as $$ [\mathbf{curl}\circ\mathbf{curl}(\mathbf{\tilde{v}})]^a=\varepsilon^{abc} \varepsilon_{cde}v^{e,d}_{\quad,b}\\ [\mathbf{curl}\circ\mathbf{curl}(\mathbf{v})]_a=\varepsilon_{abc} \varepsilon^{cde}v_{e,d}^{\quad,b} $$ or is that wrong? Realized a commaderivative upstairs is not defined. Would it be expressed with codifferential somehow? (http://en.wikipedia.org/wiki/Ricci_calculus#Raised_and_lowered_indices for summation convention)

$\endgroup$
2
$\begingroup$

I would answer to your question by collecting some facts on the structures you introduce above.

- A typo

The relations

$$\epsilon_{ijk}=\sqrt{\gamma}\epsilon_{ijk}, $$ $$\epsilon^{ijk}=\frac{1}{\sqrt{\gamma}}\epsilon^{ijk}, $$

are not true, unless $\sqrt{\gamma}=1$.

- On curl on $v=v_ie_i$.

The curl operator on vectors $v=v_ie_i$ in $\mathbb R^3$ gives the vector

$$\left(\operatorname{curl}(v)\right)_i=\epsilon_{ijk}\partial_jv_k; $$

such $\operatorname{curl}(v)$ is equal to your $\boldsymbol{\operatorname{curl}}(v)$ as $\epsilon_{ijk}=\epsilon^{ijk}$. Then

$$\boldsymbol{\operatorname{curl}}\left(\boldsymbol{\operatorname{curl}}(v)\right)_i=\operatorname{curl}(\left(\operatorname{curl}(v)\right)_i=\epsilon_{ijk}\partial_j (\epsilon_{krs}\partial_rv_s)= \epsilon_{ijk}\epsilon_{krs}\partial_j \partial_rv_s; $$

using the relations

$$\epsilon_{ijk}\epsilon_{krs}=\epsilon_{kij}\epsilon_{krs}=\delta_{ir}\delta_{js}-\delta_{is}\delta_{jr},$$

one arrives at

$$\operatorname{curl}(\left(\operatorname{curl}(v)\right)_i= (\delta_{ir}\delta_{js}-\delta_{is}\delta_{jr})\partial_j \partial_rv_s=\partial_s\partial_iv_s-\sum_r\partial^2_rv_i, $$

or

$$\boldsymbol{\operatorname{curl}}(v)=\nabla(\operatorname{div}(v))-\nabla^2(v)$$

- On curl on $\tilde{v}=v^ie_i$.

The curl operator on vectors $v=v^ie_i$ in $\mathbb R^3$, where

$$v^i=g^{in}v_n, $$

is the vector

$$\left(\boldsymbol{\operatorname{curl}}(\tilde{v})\right)_i=\epsilon_{ijk}\partial_j(g^{kn}v_n); $$

then

$$\boldsymbol{\operatorname{curl}}\left(\boldsymbol{\operatorname{curl}}(\tilde{v})\right)_i=\epsilon_{ijk}\partial_j (\epsilon_{krs}\partial_r(g^{rq}v_q))= \epsilon_{ijk}\epsilon_{krs}\partial_j (\partial_rg^{rq}v_q+g^{rq}\partial_rv_q). $$

Using once again the relations $$\epsilon_{ijk}\epsilon_{krs}=\delta_{ir}\delta_{js}-\delta_{is}\delta_{jr}$$ you can arrive at the result you are looking for.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.